Boosting Li/Na storage performance of graphite by defect engineering. Issue 36 (24th June 2021) - Ou, Mingyang; Sun, Shixiong; Liu, Yi; Xu, Yue; Chen, Chang; Hu, Pei; Fang, Chun; Li, Qing; Han, Jiantao
Abstract : The structural defects of ball-milled graphite (BMG) mainly exist as carbon atom vacancies within the graphene structure, which are proven to be the main source of lithium/sodium storage performance promotion of BMGs. Abstract : Regulating material properties by accurately designing its structure has always been a research hotspot. In this study, by a simple and eco-friendly mechanical ball milling, we could successfully engineer the defect degree of the graphite. Moreover, according to the accurate deconstruction of the structure by atomic pair distribution function analysis (PDF) and X-ray absorption near-edge structure analysis (XANES), those structural defects of the ball-milled graphite (BMG) mainly exist as carbon atom vacancies within the graphene structure, which are beneficial to enhance the lithium and sodium storage performance of BMG. Therefore, BMG-30 h exhibits superior lithium and sodium storage performance.